Retrieval of Images using Combination of Features as Color, Color Moments and Hu Moments - RAJ, RAJKUMAR; Sudhamani, Dr. M V (European Journal of Applied Sciences, 2019)
In today’s digital era, several of the image retrieval systems focus on retrieving images using features from images themselves such as color, shape and textures and are referred as low-level features. In this proposed work, the features like color with HSV color space, color moments and Hu moments are employed to retrieve similar images. Various experimentations were conducted on Wang’s database images to test the combination of features for higher performance using precision, recall, accuracy and f-score. The results obtained are compared with one another and also with existing works. The retrieval performance is found to be high for proposed system against existing works.